Getting to grips with soft contact lens handling. Issue 2 (February 2022) - Retallic, Neil; Nagra, Manbir
Abstract : Neil Retallic and Dr Manbir Nagra discuss the results of a major survey of patients concerning their challenges in handling soft contact lenses and consider how this may influence our initial instructions to patients to ensure future successful wear.